نظام ذكي لتقليص حجم وزمن عرض الفيديو - جورج كراز (Tishreen University, 2018)
تعتبر عملية الاختزال الذكية، لعرض محتويات الفيديو من الأمور الأساسية المطروحة في أدبيات الرؤيا الحاسوبية، لما لها من أهمية في تقليص الحجم اللازم لتخزين الفيديو في مختلف الوسائط، وبالأخص في الهواتف النقالة وكميرات المراقبة، وتقليص في الوقت اللازم لمشاهدة الفيديو. تتلخص عملية الاختزال الذكية، ببناء برمجية قادرة على عرض وتخزين المحتوى الهام من المشاهد، التي تحتوي على تفاصيل متجددة، إما من ناحية الصورة، أو من ناحية الصوت المرافق، وحذف المشاهد ذات المحتوى المتكرر من التفاصيل. تم في هذا البحث تقديم منهجية عمل جديدة لاستخلاص المشاهد ذات التفاصيل الجديدة في الصورة والصوت، دون التأثير على استمرارية الحركة ضمن الفيديو، وبشكل يضمن مشاهدة مستمرة؛ حيث اعتمدت منهجية العمل على خوارزميتين أساسيتين:  الخوارزمية الأولى تعمل على استخلاص المشاهد ذات التفاصيل المتغيرة في الصورة، بالاعتماد على القيم الذاتية للمشاهد، التي تبدي تغير كبير يلازم أي تغير في تفاصيل المشهد،  بينما الخوارزمية الثانية تعمل على استخلاص الصوت ذو التفاصيل المتغيرة، معتمدة على خوارزمية مقدمة عام 1985 من [1]، التي يمكنها أن تقنّع الإشارة المدروسة بغلاف ثنائي القيمة 1 أو 0،  في منطقة الإشارة المحتوية على تفاصيل يأخذ القيمة 1 ، بينما في المنطقة غير المحتوية على تفاصيل يأخذ القيمة 0. يتم تنفيذ الخوارزميتين بشكل متزامن، وبالتالي يتم استخلاص المشاهد المتغيرة، والإشارة الصوتية المرافقة لها. تمّ تطبيق منهجية العمل على مقاطع فيديو كبيرة ومتنوعة من حيث حركة الأغراض ضمنها، وحققت فعالية جيدة جداً، محققة دقة كبيرة في التزامن بين المشاهد، والصوت المرافق لها. Smart shorthand, to display video content, is one of the main problems in computer vision literature, because it is important to reduce the size of video storage in various media, especially in mobile phones and monitoring cameras, and reduce the time needed to watch video. The smart shorthand process is to build software capable of displaying and save important content from the viewer, which contains new details, either in terms of the image or in the accompanying voice and deleting scenes with repeated content. In this research, a new methodology was introduced to extract new scenes in the image and sound, without affecting the continuity of motion within the video, and in a manner that ensures continuous viewing. The methodology relied on two basic algorithms: the first algorithm works to extract scenes with variable details in the image, based on the eigenvalues of the scenes, which show a significant change in the details of the scene, while the second algorithm is based on the extraction of sound with variable details, based on the algorithm introduced in 1985 from [1], which can encode the sound signal with a double-value frame 1 or 0, in the signal area containing details that takes value 1, while in the non- Details takes value 0, the two algorithms are executed synchronously, and thus the variable scenes and the adjacent acoustic signal are drawn. The methodology used to work on large video clips in terms of movement of objects within them has achieved very good effectiveness, great accuracy in synchronization between the scenes and sound adjacent to them.